Synthesis of thiophene and N-substituted thieno[3,2-d] pyrimidine derivatives as potent antitumor and antibacterial agents - Hafez Hend N.; Alsalamah Sulaiman A.; El-Gazzar Abdel-Rhman B. A. (Acta Pharmaceutica)
A novel series of carbamothioylamino-benzene-sulfonamide-thiophene-carboxylates 4a-c and thieno[3,2-d]pyrimidin-2-yl-amino-benzene-sulfonamides 5a-c were synthesized in a series of synthetic steps and were used as key intermediates for the synthesis of thienotriazolopyrimidine-benzene-sulfonamide derivatives 6a-c and 7a-c. Thieno[3,2-d]pyrimidinones (8 and 9) were also prepared. Compound 9 was used as an intermediate for the synthesis of imidazole/1,2,4-triazole and tetrazine functionalized thieno[3,2-d]pyrimidine derivatives (10–12). Pyrrole derivatives/pyrrolopyrimidine/pyrrolotriazolopyrimidine functionalized thiophenes (15–19) were also synthesized. Structures of the newly synthesized compounds were established by elemental analysis and spectral data. Most of the newly synthesized compounds were evaluated for their in vitro activity against three human tumor cell lines, namely, liver cancer (HepG-2), colon cancer (HT-29) and lung cancer (NCI-H460), using doxorubicin as standard. Compounds 16 (GI50 = 0.02, 0.04 and 0.06 μmol L−1, resp.) and 19b (GI50 = 0.02, 0.03 and 0.05 μmol L−1, resp.) showed higher activity against all cell lines than doxorubicin. Most of the compounds were also screened for antibacterial activity using ciprofloxacin as standard drug. Compounds 4b and 6b, both containing benzenesulfonamide linked to N-, 10 bearing imidazole moiety, and 15 and 19b,c with a thiophene-2-carboxylic acid chain, exhibited high activity against Gram-positive and Gram-negative bacteria.